Dryland field validation of genotypic variation in salt tolerance of chickpea (Cicer arietinum L.) determined under controlled conditions - Turner, N.C.; Quealy, J.; Stefanova, Katia; Pang, J.; Colmer, T.D.; Siddique, K.H.M. (2022)
Chickpea (Cicer arietinum L.) is a moderately salt-susceptible grain legume species. Genotypic differences in salt tolerance/susceptibility have been identified in chickpea genotypes grown in adequately-watered soil in pots with different salt concentrations, but few studies have been conducted in saline fields. This three-year study compared the growth and yield of chickpea genotypes to determine whether genotypic differences in salt tolerance/susceptibility identified in glasshouse pot experiments applied when grown in a dryland saline field. The emergence, phenology, growth, leaf ion concentration, yield and yield components of 10–20 chickpea genotypes were compared under controlled saline and water conditions in the glasshouse, and saline and non-saline conditions in the field in a semiarid environment. In the field, soil salinity and yields varied from year to year in the non-saline and saline treatments. Genotypic differences in salt tolerance and sensitivity were observed in the controlled salt and water conditions in the glasshouse. The salt tolerant and salt sensitive check genotypes, GENESIS 836 and RUPALI, respectively, grown in all three comparison years were similarly tolerant and sensitive in the glasshouse and dryland field in all three comparison years. However, other genotypes selected for salt tolerance under controlled conditions were not observed to be tolerant in the dryland field. While salinity slowed the rate of emergence and increased the time to flowering, the variation in saline yields among genotypes was associated with aboveground biomass, filled pod number and seed number at maturity in both the glasshouse and field, but not the number of emerged plants that survived to maturity or the delay in flowering. Salinity significantly increased the leaf Na+, K+ and Cl- concentrations in the glasshouse and field (except in the glasshouse in 2010). Na+ increased in young and old leaves by 28–84%, but the concentrations of Na+ or K+ in the leaves across genotypes was not correlated with yield in saline soil. Salinity increased leaf Cl– concentrations by 80–290%; the increase in young leaves had a significant association with reduced yield among genotypes only in the glasshouse in one year. We conclude that selection under controlled soil salinity and water content in pots can identify some genotypes that are salt tolerant, but for dryland saline environments verification of their tolerance in comparable environments is essential.